Delays in Obtaining Abortion and Miscarriage Care Among Pregnant Persons in New York State During the COVID-19 Pandemic: The CAP Study - Sarah Pickering; Meredith Manze; Jessie Losch; Diana Romero (Women's Health Reports)
Background: We sought to investigate delays obtaining abortion and miscarriage care during the COVID-19 pandemic, compared with before the pandemic, among pregnant persons in New York State (NYS). Methods: We administered a cross-sectional survey in June–July 2020 to NYS residents aged 18–44 years who identified as female or transgender male (N = 1,525). This analysis focused on a subsample who had an abortion or miscarriage during COVID-19, were seeking an abortion at the time of the survey, or had an abortion or miscarriage before COVID-19 (n = 116). We conducted bivariate analyses to determine differences in delays to seeking or obtaining an abortion or miscarriage during versus before the pandemic, as well as consideration of abortion among those pregnant during versus before the pandemic. We also asked open-ended questions about miscarriage and abortion experiences. Main Findings: Of the 21 respondents who sought or were seeking an abortion during the COVID-19 pandemic, 76.2% (n = 16) reported experiencing a delay in obtaining abortion care, compared with 18.2% (n = 4) of those who experienced a delay before the pandemic (p < 0.001). A significantly higher proportion of respondents who were pregnant during the pandemic considered abortion, compared with those who gave birth before the pandemic (39.1% vs. 7.6%; p < 0.001). Of the 39 respondents who miscarried during the pandemic, 35.9% (n = 14) delayed care, compared with 5.9% (n = 2) before the pandemic (p < 0.01). Some respondents also commented on the difficulty of accessing miscarriage services during COVID-19 in open-ended responses. Principal Conclusions: Those who sought abortion or miscarriage care during the COVID-19 pandemic experienced significant delays in getting care. These are essential services that must be available during public health emergencies, and yet access to these services is now severely limited in many states due to the Dobbs vs. Jackson Women's Health Organization decision.